Peta Dukungan Pemilih Pada Pemilihan Bupati Dan Wakil Bupati Kabupaten Bandung Tahun 2010 - Kartini, Dede Sri (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2011)
The result of Local Election in Bandung District on 2010 has shown some tendency on voting behavior. Findings in the first roud election indicate that some candidates dominate certain sub districts where they live. In the second round there is some votersâ€™ movement because some candidates donâ€™t pass to the second round. Some voters who choose candidate from PDIP coalition in first round change their preference to candidate from Golkar coalition in second round. Meanwhile sub-districts who won by candidate from PKB coalition in the first round has moved to candidate from Golkar coalition and PKS coalition in the second round. It can be concluded that there is â€œpolitical thinkingâ€ phenomena in Bandung District. Voters who prefer candidate from Moslem Party (PKB coalition) will vote candidate from other Moslem Party (PKS coalition), whereas voters who prefer candidate from Nationalist Party (PDIP coalition) will vote candidate from Developmentalism Party (Golkar ). It took more depth research to dig up the existence of political thinking.